2014
DOI: 10.1177/0883073814553271
|View full text |Cite
|
Sign up to set email alerts
|

Association of Copy Numbers of Survival Motor Neuron Gene 2 and Neuronal Apoptosis Inhibitory Protein Gene With the Natural History in a Chinese Spinal Muscular Atrophy Cohort

Abstract: We evaluated survival motor neuron 2 (SMN2) and neuronal apoptosis inhibitory protein (NAIP) gene copy distribution and the association of copy number with survival in 232 Chinese spinal muscular atrophy (SMA) patients. The SMN2 and NAIP copy numbers correlated positively with the median onset age (r = 0.72 and 0.377). The risk of death for patients with fewer copies of SMN2 or NAIP was much higher than for those with more copies (P < .01). The survival probabilities at 5 years were 5.1%, 90.7%, and 100% for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 28 publications
0
36
1
Order By: Relevance
“…Our previous study showed that cases with homozygous deletion variants phenotypically have type II or III SMA when they also have three copies of SMN2. 10 Thus, it is possible that the increased number of SMN2 gene copies alleviated the phenotype in this child.…”
Section: Influencing the Correct Splicing Of Smn1mentioning
confidence: 94%
“…Our previous study showed that cases with homozygous deletion variants phenotypically have type II or III SMA when they also have three copies of SMN2. 10 Thus, it is possible that the increased number of SMN2 gene copies alleviated the phenotype in this child.…”
Section: Influencing the Correct Splicing Of Smn1mentioning
confidence: 94%
“…NAIP was given its name because it bore a baculoviral IAP repeat (BIR) domain, and was initially thought to regulate survival of neurons. While NAIP loss in neurons, or other cells, is not the main cause of SMA, it does appear to modify the severity of the disease depending on the gene copy numbers present [84]. The closest mouse homologue is Naip2.…”
Section: The Naip Gene Familymentioning
confidence: 97%
“…In a study of Chinese patients, Fang et al21 compared copy numbers of SMN1 , SMN2 , and NAIP in SMA patients and healthy controls and produced evidence of differences in copy numbers and gene structure between the SMA patients and controls. Qu et al22 further investigated the association of copy numbers of SMN2 and NAIP with the disease course in SMA patients, and found that patients with fewer copies of SMN2 and NAIP were characterized by a higher risk of death and a lower survival rate.…”
Section: Discussionmentioning
confidence: 99%